2011
DOI: 10.1590/s0100-72032011001100006
|View full text |Cite
|
Sign up to set email alerts
|

Associação de gravidez na adolescência e prematuridade

Abstract: Janne eyre fernandes brito da costa 4 vanda maria ferreira siMões 5Resumo OBJETIVO: Analisar a associação da gravidez na adolescência com prematuridade. MÉTODOS: Foram incluídas todas as pacientes que pariram num hospital terciário universitário do Maranhão, no período de julho a dezembro de 2006, alocando-as em dois grupos: adolescentes (10 a 19 anos de idade) e adultas (20 a 34 anos). As variáveis estudadas foram: escolaridade, situação conjugal, número de consultas no pré-natal, idade gestacional no início … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1
36

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 20 publications
(54 reference statements)
4
9
1
36
Order By: Relevance
“…Adolescent women (under the age of 20) and those with an advanced age (older than 34 years old) presented an association with premature delivery, corroborating to the existing literature (9)(10)(11)(12)(13) . A cross-sectional study conducted in Feira de Santana-BA showed that the risk of premature birth increased with the decrease in the mother's age, which can reach a relative risk of 10 times higher in women up to the age of 16 years old (14) .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Adolescent women (under the age of 20) and those with an advanced age (older than 34 years old) presented an association with premature delivery, corroborating to the existing literature (9)(10)(11)(12)(13) . A cross-sectional study conducted in Feira de Santana-BA showed that the risk of premature birth increased with the decrease in the mother's age, which can reach a relative risk of 10 times higher in women up to the age of 16 years old (14) .…”
Section: Discussionsupporting
confidence: 87%
“…A cross-sectional study conducted in Feira de Santana-BA showed that the risk of premature birth increased with the decrease in the mother's age, which can reach a relative risk of 10 times higher in women up to the age of 16 years old (14) . In another study, even in places with higher incomes, women over the age of 40 had 2.6 more premature deliveries out of 100 births than women between the age of 25 and 29 years old (12) . At the Teaching Hospital in Maranhão, prematurity occurred in a greater percentage among adolescents at 21.4%, while it was 15.7% among adults (10) .…”
Section: Discussionmentioning
confidence: 89%
“…In the present study it was evident that the behavior of the Adolescent group was similar to that of the Adult group regarding the perinatal results, albeit showing, in both groups, less than ideal maternal-infant healthcare figures related to the averages reported in Brazilian data (28) . This suggests that in a needy population, social factors demand even more attention than the biological factors.…”
Section: Discussionsupporting
confidence: 58%
“…On the other hand, Simões et al (27) , even after adjustment of reproductive and socioeconomic factors, found an association between maternal age <18 years and prematurity, a fact also reported by Martins et al (28) . The incidence of low birth weight showed no significant difference between the two groups of mothers; however, it is relatively high if compared to the Health Report 2004, in which the Southeast Region showed a percentage of 8%, and the South Region of 8.1% (29) .…”
Section: Discussionmentioning
confidence: 58%
“…No mundo, atualmente, a prematuridade representa a principal causa de mortalidade neonatal com um percentual de 75% (2,3) . As prevalências de prematuridade no mundo, no Brasil e no Maranhão são de 9,2%; 7,1%; e 17,3%, respectivamente (4,5) . Além das repercussões clínicas, existem ainda as implicações econômicas associadas a esse evento, uma vez que demanda cuidados de maior complexidade que devem ser tomados mesmo depois do período neonatal, muitas vezes por toda a vida, devido a sequelas causadas pela prematuridade (6) .…”
Section: Introductionunclassified